2021
DOI: 10.1002/jor.25006
|View full text |Cite
|
Sign up to set email alerts
|

Development of a murine model of ischemic osteonecrosis to study the effects of aging on bone repair

Abstract: Age at onset is one of the most important predictors of outcome following ischemic osteonecrosis (ON). Currently, there is no well‐established animal model to study the effects of age on the repair process following ischemic ON. The purpose of this study was to further advance a murine model of ischemic ON using four age groups of mice to determine the effects of aging on revascularization and bone repair following ischemic ON. Ischemia was surgically induced in the distal femoral epiphysis of four age groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In young animal models, Perthes disease may be induced through the ischemic osteonecrosis of the femoral head by ligation of the femoral neck. Yamaguchi et al ( 62 ) showed that in piglets, a model of ischemic osteonecrosis of the femoral head can be constructed by ligating the femoral neck, cutting off the round ligament, and implementing supra knee amputation at the junction of the distal epiphysis and epiphysis of the femur. In this model, the IL-6 receptor monoclonal antibody can reduce hip synovitis and osteoclast bone resorption, and increase bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In young animal models, Perthes disease may be induced through the ischemic osteonecrosis of the femoral head by ligation of the femoral neck. Yamaguchi et al ( 62 ) showed that in piglets, a model of ischemic osteonecrosis of the femoral head can be constructed by ligating the femoral neck, cutting off the round ligament, and implementing supra knee amputation at the junction of the distal epiphysis and epiphysis of the femur. In this model, the IL-6 receptor monoclonal antibody can reduce hip synovitis and osteoclast bone resorption, and increase bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Rat models of steroid induction of ANFH under hypoxic conditions [46], surgical induction of ANFH considering ageing and bone repair [47], and ANFH induction caused by tobacco smoke [48] have been reported since 2020. By using the appropriate rat model for the induction of ANFH which suits the disease characteristics (mechanism, purpose of study, and bone condition) of interest, the relevant mechanisms of action can be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated to obtain 80% power with alpha ​= ​0.05 and large effect-size (i.e., Cohen's d ​> ​0.8–0.9) based on our previous study [ 10 ]. JIO was surgically induced on the distal femoral epiphysis under isoflurane anesthesia, as previously described [ 22 , 23 ]; this model produced almost 100% ON in immature [ 22 ] and adolescent mice [ 23 ]. Briefly, the blood vessels supplying the right distal femoral epiphysis (i.e., a branch of the popliteal vessel and branches of the medial, central, and lateral genicular vessels) were identified and cauterized.…”
Section: Methodsmentioning
confidence: 99%
“…The distal femoral epiphyses were fixed with 10% formalin, decalcified in 10% EDTA for 5 days, embedded in paraffin, cut into 5 ​μm sections, and stained [ 9 , 22 , 23 ]. H&E staining was performed according to a standard protocol [2 weeks (saline; n ​= ​7, MR16-1; n ​= ​8), 4 weeks (saline; n ​= ​13, MR16-1; n ​= ​15)] ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%